2016
DOI: 10.18203/2320-1770.ijrcog20160566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of the antifertility potential activity and adverse effects of Trigonella foenum-graecum seeds and combined oral contraceptive pills in female rats

Abstract: Background: Antifertility agents are one of the most common medication used in this modern era. In this research we used herbal plant Trigonella foenum-graecum (fenugreek) seeds to study the antifertility activity of Fenugreek Seeds allowed aqueous (FSA) extract in female rats compared with marketed combined oral contraceptive pills (COCPs) by evaluating Follicle Stimulating Hormone (FSH) level and to detect the adverse effects by determining the uterine weight, implantation rate, endometrial thickness, endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fenugreek seeds estrogenic activity in ovariectomized female rats against breast and colon cancer [4][5][6][7]. Other studies has shown that fenugreek seeds have fertility regulating properties [8][9][10]. The aim of this study was to evaluate the estrogenic activity of fenugreek seeds in ovariectomized rats, by using uterotrophic assays that combined the analysis of morphological, histological, biochemical and molecular endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Fenugreek seeds estrogenic activity in ovariectomized female rats against breast and colon cancer [4][5][6][7]. Other studies has shown that fenugreek seeds have fertility regulating properties [8][9][10]. The aim of this study was to evaluate the estrogenic activity of fenugreek seeds in ovariectomized rats, by using uterotrophic assays that combined the analysis of morphological, histological, biochemical and molecular endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, the various medical benefits of fenugreek have been extensively studied 18 with further emphasis on its effects on female gonadal hormones and their reproductive functions. 19,20 It reduces the serum levels of E2 and the number of ovarian follicles. 21,22 Moreover, recent studies found that fenugreek can reduce VP by decreasing VEGF expression in hepatocyte cytoplasm.…”
Section: Introductionmentioning
confidence: 99%